The naked gun (2025) [videorecording (Blu-Ray)] - Schaffer, Akiva, 1977-; Gregor, Dan; Mand, Doug; Neeson, Liam; Anderson, Pamela; Hauser, Paul Walter, 1986-; Durand, Kevin; Huston, Danny, 1962-; Pounder, C. C. H.; Rhodes, Cody, 1985-; Koshy, Liza, 1996-; Yu, Eddie (Paramount, 2025)
Only one man has the particular set of skills -- to lead Police Squad and save the world.